2017
DOI: 10.1038/s41598-017-05727-w
|View full text |Cite
|
Sign up to set email alerts
|

The miR-29 transcriptome in endocrine-sensitive and resistant breast cancer cells

Abstract: Aberrant microRNA expression contributes to breast cancer progression and endocrine resistance. We reported that although tamoxifen stimulated miR-29b-1/a transcription in tamoxifen (TAM)-resistant breast cancer cells, ectopic expression of miR-29b-1/a did not drive TAM-resistance in MCF-7 breast cancer cells. However, miR-29b-1/a overexpression significantly repressed TAM-resistant LCC9 cell proliferation, suggesting that miR-29b-1/a is not mediating TAM resistance but acts as a tumor suppressor in TAM-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 64 publications
0
32
1
Order By: Relevance
“…Concordant with our findings, miR-210 overexpression was associated with worse prognosis in multiple studies and systematic reviews (4, 5, 37-39) and likely characterizes an aggressive phenotype. The miR-29 family is reported to exhibit both tumor-suppressing and -promoting roles in breast cancer (40)(41)(42)(43). In our study, higher levels of miR-29c were associated with worse prognosis, in contrast to published findings in triple-negative breast cancer, where higher miR-29c levels were associated with better prognosis (44)(45)(46)(47).…”
Section: Discussioncontrasting
confidence: 68%
“…Concordant with our findings, miR-210 overexpression was associated with worse prognosis in multiple studies and systematic reviews (4, 5, 37-39) and likely characterizes an aggressive phenotype. The miR-29 family is reported to exhibit both tumor-suppressing and -promoting roles in breast cancer (40)(41)(42)(43). In our study, higher levels of miR-29c were associated with worse prognosis, in contrast to published findings in triple-negative breast cancer, where higher miR-29c levels were associated with better prognosis (44)(45)(46)(47).…”
Section: Discussioncontrasting
confidence: 68%
“…Exosomes from TAM-resistant LCC2 cells, derived from MCF-7 cells, had higher levels of the lncRNA UCA1 than parental MCF-7 cells, and the incubation of MCF-7 cells with exosomes from LCC2 cells conferred TAM-resistance [336]. We reported that miR-29b-1/a directly targets ATP synthase subunit genes ATP5G1 and ATPIF1 and inhibit OCR and decrease ATP in MCF-7 and LCC9 breast cancer cells [337]. UCA1 activates AKT-mTOR signaling [338] and is a ceRNA for miR-18a, thus derepressing HIF-1α [137].…”
Section: Micro Rnas and Long Non-coding Rnas In Extracellular Vesimentioning
confidence: 99%
“…This tumour suppressive role was mediated through targetting of SPIN1 effecting the downstream signaling of WNT/β-catenin and Akt. Furthermore the miR-29 family also acts as a tumour supressor in tamoxifen resistant breast cancer cells inhibiting cell proliferation through repressing genes involved in mitochondrial bioenergetics [ 30 , 31 ]. These data strengthen our finding that high expression of this miRNA is a biomarker for good prognosis.…”
Section: Discussionmentioning
confidence: 99%